Thermoreversible crystallization-driven aggregation of diblock copolymer nanoparticles in mineral oil. Issue 17 (9th April 2018) - Derry, Matthew J.; Mykhaylyk, Oleksandr O.; Ryan, Anthony J.; Armes, Steven P.
Abstract : Poly(behenyl methacrylate)-stabilized diblock copolymer nanoparticles are prepared in mineral oil via polymerization-induced self-assembly. Such nanoparticles are colloidally stable at 50 °C but undergo reversible crystallization-driven aggregation at 25 °C. Abstract : A poly(behenyl methacrylate)37 (PBeMA37 ) macromolecular chain transfer agent is utilized for the reversible addition–fragmentation chain transfer (RAFT) dispersion polymerization of benzyl methacrylate (BzMA) directly in mineral oil at 90 °C. Polymerization-induced self-assembly (PISA) occurs under these conditions, yielding a series of sterically-stabilized PBeMA37 –PBzMA x diblock copolymer spheres of tunable diameter as confirmed by dynamic light scattering (DLS) and transmission electron microscopy (TEM) studies. Rheological studies indicate that a relatively transparent, free-flowing, concentrated dispersion of non-interacting 32 nm PBeMA37 –PBzMA100 spheres at 50 °C forms a turbid, paste-like dispersion on cooling to 20 °C. Turbidimetry and differential scanning calorimetry (DSC) studies conducted on solutions of PBeMA37 homopolymer in mineral oil suggest that this switchable colloidal stability is linked to crystallization-induced phase separation exhibited by this stabilizer block. Indeed, variable-temperature small-angle X-ray scattering (SAXS) indicates that a loose mass fractal network of strongly interacting spheres is formed on cooling to 20 °C, which accounts for this thermoreversible sol–gel transition. Moreover, SAXS, DSC and wide-angle X-ray scattering (WAXS) analyses indicate that the behenyl (C22 H45 ) side-chains first form crystalline domains comprising adjacent stabilizer chains within individual spherical nanoparticles, with subsequent crystallization between neighboring nanoparticles leading to the formation of the mass fractal aggregates.